Questions kids ask about everyday life - Comely, Richard; Dickie, Alison (Grolier Toronto, 1989)
Questions Kids Ask About Everyday Life offers simple and engaging explanations to help children understand common aspects of daily life, from routines to practical concepts, fostering curiosity and learning.